NiS1.97: a new efficient water oxidation catalyst for photoelectrochemical hydrogen generation - Bhosale, Reshma; Kelkar, Sarika A.; Parte, Golu; Fernandes, Rohan; Kothari, Dushyant; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2015)
NiS1.97, a sulfur-deficient dichalcogenide, in nanoscale form, is shown to be a unique and efficient photoelectrochemical (PEC) catalyst for H-2 generation by water splitting. Phase pure NiS1.97 nanomaterial is obtained by converting nickel oxide into sulfide by controlled sulfurization method, which is otherwise difficult to establish. The defect states (sulfur vacancies) in this material increase the carrier density and in turn lead to favorable band line-up with respect to redox potential of water, rendering it to be an effective photoelectrochemical catalyst. The material exhibits a remarkable PEC performance of 1.25 mA/cm(2) vs NHE at 0.68 V in neutral pH, which is almost 1000 times superior as compared with that of the stoichiometric phase of NiS2. The latter is well-known to be a cocatalyst but not as a primary PEC catalyst.
Keywords: dichlacogenide; Faradaic efficiency; Hydrogen generation; NiS1.97; nonstoichiometric; photoelectrochemical catalyst; sulfurization

Hybrid perovskite quantum nanostructures synthesized by electrospray antisolvent-solvent extraction and intercalation - Naphade, Rounak; Nagane, Satyawan; Shanker, G. Shiva; Fernandes, Rohan; Kothari, Dushyant; Zhou, Yuanyuan; Padture, Nitin P.; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2016)
Perovskites based on organometal lead halides have attracted great deal of scientific attention recently in the context of solar cells and optoelectronic devices due to their unique and tunable electronic and optical properties. Herein, we show that the use of electrospray technique in conjunction with the antisolventsolvent extraction leads to novel low-dimensional quantum structures (especially 2-D nanosheets) of CH3NH3PbI3- and CH3NH3PbBr3-based layered perovskites with unusual luminescence properties. We also show that the optical bandgaps and emission characteristics of these colloidal nanomaterials can be tuned over a broad range of visible spectral region by compositional tailoring of mixed-halide (I- and Br-based) perovskites.
Keywords: 2D nanostructure systems; antisolvent-solvent extraction; bandgap tuning; electrospray; nanosheets; perovskite; quantum dots

Minute-made activated porous carbon from agro-waste for Li-ion battery anode using a low power microwave oven - Agarkar, Shruti; Yadav, Poonam; Fernandes, Rohan; Kothari, Dushyant; Suryawanshi, Anil; Ogale, Satishchandra (Electrochimica ACTA, 2016)
We demonstrate a very simple, cost-effective and superfast process for making Li-ion battery (LIB) anode grade carbon from agro-waste in the form of sugarcane bagasse using a low power microwave system. Activation of this bagasse derived carbon is carefully optimized by using various weight ratios of KOH to obtain the desired properties of functional carbon in terms of porosity and electrical conductivity. Low equivalent series resistance (ESR), low charge transfer resistance with good electrical conductivity, and optimum porosity for efficient ion diffusion make this carbon a good candidate for Li-ion battery anode material rendering a reversible capacity of 757 mAhg (1) at a current density of 100 mAg (1) and a good cycling performance at high current rates. (C) 2016 Elsevier Ltd. All rights reserved.